2020
DOI: 10.1038/s41531-019-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease: proteinopathy or lipidopathy?

Abstract: Lipids play a more significant role in Parkinson’s disease and its related brain disorders than is currently recognized, supporting a “lipid cascade”. The 14 kDa protein α-synuclein (αS) is strongly associated with Parkinson’s disease (PD), dementia with Lewy bodies (DLB), other synucleinopathies such as multiple system atrophy, and even certain forms of Alzheimer’s disease. Rigorously deciphering the biochemistry of αS in native systems is the key to developing treatments. αS is highly expressed in the brain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
166
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 123 publications
9
166
0
Order By: Relevance
“…When looking at these findings together, it is evident that LDs and lipid homeostasis play a more significant role in PD than originally thought. This line of thought is supported by Fanning et al (2020) who stated that α-synuclein toxicity and cell trafficking defects have been associated with aberrations in LD content and distribution. PD has classically been believed to be a "proteinopathy, " but with many of the recent discoveries, lipid dyshomeostasis is rapidly becoming one of the fundamental characteristics of this disease (Fanning et al, 2020).…”
Section: Parkinson's Diseasementioning
confidence: 81%
“…When looking at these findings together, it is evident that LDs and lipid homeostasis play a more significant role in PD than originally thought. This line of thought is supported by Fanning et al (2020) who stated that α-synuclein toxicity and cell trafficking defects have been associated with aberrations in LD content and distribution. PD has classically been believed to be a "proteinopathy, " but with many of the recent discoveries, lipid dyshomeostasis is rapidly becoming one of the fundamental characteristics of this disease (Fanning et al, 2020).…”
Section: Parkinson's Diseasementioning
confidence: 81%
“…Here we describe very different and much larger assemblies that have not been previously reported, and which form specifically in the presence of lipid vesicles. This is particularly interesting given the emerging discussion over whether Parkinson's disease (PD) is a proteinopathy or lipidopathy 20 . These newly reported structures are able to be readily viewed using transmission EM (TEM) and range in polymorph from structures that are ribbon like to those that are highly helical and compact, with a range of observed helical assemblies in between.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid dysregulation including lipid droplets dyshomeostasis have been reported to be part of glial cells' stress response during neurodegeneration processes 5,7-9 and in the context of PD 39 . Here, we found that SPEN/SHARP belongs to the set of astrocyteexpressed genes which mRNA levels are significantly different in the substantia nigra of PD patients as compared to controls.…”
Section: Discussionmentioning
confidence: 99%